1995
DOI: 10.1083/jcb.129.4.1093
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of alpha-dystroglycan during embryonic nerve-muscle synaptogenesis.

Abstract: Abstract. The distribution of ot-dystroglycan (aDG) relative to acetylcholine receptors (ACHEs) and neural agrin was examined by immunofluorescent staining with mAb IIH6 in cultures of nerve and muscle cells derived from Xenopus embryos. In Western blots• probed with mAb IIH6, o~DG was evident in membrane extracts of Xenopus muscle but not brain, c~DG immunofluorescence was present at virtually all synaptic clusters of ACHEs and neural agrin. Even microclusters of ACHEs and agrin at synapses no older than 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 53 publications
(86 reference statements)
6
61
0
Order By: Relevance
“…24,25 After 24 hours, the percentage of late apoptotic F4/80 ϩ cells was evaluated by flow cytometry. This experiment showed that the antibody-mediated blocking of agrin-␣-DG interactions enhanced apoptosis ( Figure 6A) and that this effect required agrin expression, because the antibody failed to enhance apoptosis in splenocyte cultures obtained from agrindeficient mice ( Figure 6A).…”
Section: Agrin Delivers Survival Signals Through the ␣-Dg Receptormentioning
confidence: 99%
“…24,25 After 24 hours, the percentage of late apoptotic F4/80 ϩ cells was evaluated by flow cytometry. This experiment showed that the antibody-mediated blocking of agrin-␣-DG interactions enhanced apoptosis ( Figure 6A) and that this effect required agrin expression, because the antibody failed to enhance apoptosis in splenocyte cultures obtained from agrindeficient mice ( Figure 6A).…”
Section: Agrin Delivers Survival Signals Through the ␣-Dg Receptormentioning
confidence: 99%
“…MuSK aggregates and co-localizes with AChRs [Fuhrer et al, 1997], is required for neuromuscular synapse formation and in the adult is found only at neuromuscular synapses [Valenzuela et al, 1995]. Another molecule that aggregates and colocalizes with AChRs is ·-dystroglycan [Campanelli et al, 1994;Sugiyama et al, 1994;Apel et al, 1995;Cohen et al, 1995], which is necessary for the stabilization of AChR clusters at neuromuscular synapses [Jacobson et al, 2001]. The interaction of ·-dystroglycan with the extracellular matrix molecule laminin appears to be cru-cial for linking extracellular components to the intracellular actin cytoskeleton in vivo [Ervasti and Campbell, 1993; reviewed by Campbell, 1995].…”
Section: Introductionmentioning
confidence: 99%
“…Homologs have been identified in a range of organisms including mammals (Ibraghimov-Beskrovnaya et al, 1992), chicken (Brancaccio et al, 1995), zebrafish (Parsons et al, 2002), Xenopus (Cohen et al, 1995), Drosophila (Greener and Roberts, 2000), and nematodes (Grisoni et al, 2002).…”
Section: Introductionmentioning
confidence: 99%